Subcortical brain iron deposition in individuals with schizophrenia. (July 2022) - Sonnenschein, Susan F.; Parr, Ashley C.; Larsen, Bart; Calabro, Finnegan J.; Foran, William; Eack, Shaun M.; Luna, Beatriz; Sarpal, Deepak K.
Abstract: Subcortical structures play a critical role the pathophysiology and treatment of schizophrenia (SZ), yet underlying neurophysiological processes, in vivo, remain largely unexplored. Brain tissue iron, which can be measured with magnetic resonance-based methods, is a crucial component of a variety of neuronal functions including neurotransmitter synthesis. Here we used a proxy measure of tissue iron to examine basal ganglia and thalamic structures in an adult cohort of individuals with chronic SZ. A publicly available dataset of 72 individuals with SZ between ages 18 and 65, and a matched sample of 74 healthy control (HC) participants were included. A novel method that calculated the inverse-normalized T2*-weighted contrast (1/nT2*) was used to estimate brain iron within the basal ganglia and thalamus. Between group, age- and sex-related differences in 1/nT2* were examined, in addition to correlations with measures of psychopathology and cognition. Individuals with SZ showed greater 1/nT2* (iron index) compared to HCs in the thalamus (p < 0.01, FWE corrected). Age-related 1/nT2* accumulation was noted in regions of the basal ganglia, coinciding with prior work, and prominent sex-differences were noted in the caudate and thalamus (p < 0.01, FWE corrected). No significant relationship was observed between 1/nT2* and measures of neurocognition or psychopathology. Overall, our findings characterize a non-invasive proxy measure of tissue iron in SZ and highlight thalamic iron accumulation as a potential marker of illness.